Relationships between knowledge management and ecodesign: a theoretical analysis - Lima, Pedro Augusto Bertucci [UNESP]; Furlan, Marcelo; Leoni, Luna; Domingues, Ana Mariele [UNESP]; Jorge, Carlos Francisco Bitencourt [UNESP]; Jugend, Daniel [UNESP] (Taylor & Francis, 2025)
Ecodesign is an important approach for companies to improve their environmental performance, as it impacts the whole product life cycle. Although many studies have investigated the contributions of knowledge management (KM) to the new product development process, there are still few that focus specifically on its relationship with ecodesign. With the aim of contributing to the debate, this study sought to identify and analyse relationships between ecodesign and KM through the systematic literature review of 29 articles. The results indicate that many studies in the area have been based on KM processes and the SECI model. Collaborations with external actors, such as universities and suppliers, and the application of digital technologies and life cycle assessments, have been shown to be important for strengthening the relationships between KM and ecodesign. Additionally, the adoption of cross-functional teams that include sustainability experts may also improve the relationships between KM and ecodesign.
Keywords: circular economy; ecodesign; Knowledge management; sustainability